Biodiversity of a Permian temperate forest: A case study from Ustali area, Ib River Basin, Odisha, India. (13th September 2020) - Patel, Roshni; Goswami, Shreerup; Sahoo, Mrutyunjaya; Pillai, Sankar Suresh Kumar; Aggarwal, Neha; Mathews, Runcie Paul; Swain, Ramani Ranjan; Saxena, Anju; Singh, Kamal Jeet
Abstract : A palaeofloristic study and geochemical analysis of a Permian section in Ib River Basin near Ustali village, Odisha State has been undertaken. The complete macrofloral assemblage comprising 44 taxa belong to the orders Equisetales, Sphenophyllales, Filicales, and Glossopteridales . A marked floral change has been noticed in two fossiliferous horizons of this section, demonstrating the existence of two different floral zones in Raniganj Formation rocks of this section. The upper floral zone is assigned to the Wuchiapingian, while the lower floral zone is of Wordian‐Capitanian age. The occurrence of Gangamopteris is the first report of this genus from the Raniganj Formation of the Ib River Basin, as well as from the Son‐Mahanadi Master Basin. The existence of tiny seeds infers the prevalence of arid and warm climatic conditions at least during the blossoming and seed development phase, resulting in a sluggish inflow of nutrients to the growing seeds, thereby restricting their proper growth. The palynoassemblage confirms its resemblance with the Raniganj palynoflora of Wordian‐Capitanian affinity. Biomarker analysis indicates a good contribution of algal and microbial organic matter during the deposition, however, the overall biomarker composition and distribution suggests an increased thermal maturity of the studied samples. Abstract :